Wealthy, healthy and green: Are we there yet?. (November 2021) - Nghiem, Son; Tran, Bach; Afoakwah, Clifford; Byrnes, Joshua; Scuffham, Paul
Highlights: Applied cub-convergence test and panel data analysis on OECD data in 1990–2015 period. There was no significant evidence of overall convergence except for Carbon monoxide and Nitrogen oxides. Convergence occurred among groups of countries in all three aspects. Human capital is crucial to achieving the balance between healthy, wealthy and green. Abstract: The history of humankind witnessed a continual improvement of living standards. The introduction of agriculture stabled our food supplies. The industrial revolution eradicated hunger and reduced poverty across the globe. During the development process, human also reached the capacity to create substantial impacts on the environment, which has created adverse effects on our health. We believe that technological progress will enable us to achieve a balance between health, income and the environment. In this study, we test the club convergence hypothesis using data on economic development, health and environment of 36 OECD countries during the 1990–2015 period. Using the club convergence test, we found significant evidence of overall convergence only in the emission of two air pollutants: Carbon monoxide and Nitrogen oxides. However, groups of countries have converged in all three aspects. Also, our panel data analysis showed that improving human capital is crucial for the synergy between good health, clean environment and positive economic growth.